Disease modifying agents of myeloproliferative neoplasms: a review - Lee, Sung-Eun (Blood Res, 2021)
The identification of driver mutations in Janus kinase (JAK) 2, calreticulin (CALR), and myeloproliferative leukemia (MPL) has contributed to a better understanding of disease pathogenesis by highlighting the importance of JAK signal transducer and activator of transcription (STAT) signaling in classical myeloproliferative neoplasms (MPNs). This has led to the therapeutic use of novel targeted treatments, such as JAK2 inhibitors. More recently, with the development of next-generation sequencing, additional somatic mutations, which are not restricted to MPNs, have been elucidated. Treatment decisions for MPN patients are influenced by the MPN subtype, symptom burden, and risk classification. Although prevention of vascular events is the main objective of therapy for essential thrombocythemia (ET) and polycythemia vera (PV) patients, disease-modifying drugs are needed to eradicate clonal hematopoiesis and prevent progression to more aggressive myeloid neoplasms. JAK inhibitors are a valuable therapeutic strategy for patients with myelofibrosis (MF) who have splenomegaly and/or disease-related symptoms, but intolerance, refractory, resistance, and disease progression still present challenges. Currently, allogeneic stem cell transplantation remains the only curative treatment for MF, but it is typically limited by age-related comorbidities and high treatment-related mortality. Therefore, a better understanding of the molecular pathogenesis and potential new therapies with the aim of modifying the natural history of the disease is important. In this article, I review the current understanding of the molecular basis of MPNs and clinical studies on potential disease-modifying agents.